Should the earned income tax credit rise for childless adults? - Harry J. Holzer (IZA World of Labor, 2023)
The earned income tax credit provides important benefits to low-income families with children. At substantial costs (over 70 billion to the US federal government), it increases the incomes of such families while encouraging parents to work more by subsidizing their incomes. But low-income adults without children and non-custodial parents receive very low payments under the program in most years (except fo 2021). Many of these adults are less-educated men, whose labor force participation rates and relative wages have been declining for years. They might benefit significantly from a more generous earned income tax credit for childless adults
Keywords: J38; 330; employment; less-educated men; childless; low-income adults; non-custodial parents